Emerging trends regarding accessible accommodation in Dubai luxury hotels. (5th August 2014) - Morris, Stephanie; Kazi, Scholah
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to determine how luxury hotel operators in Dubai interpret the current disability laws in the region, and further how they currently provide accessible accommodation to disabled tourists. Design/methodology/approach – This study draws on data collected using document analysis of UAE Federal Law 29 (English translation), Department of Tourism and Commerce Marketing Hotel Classification Manual, some five star hotels' internal guidelines and semi-structured interviews with 12 hotel representatives. Findings – The majority of participants were unaware of existing statutory law addressing the rights and needs of the disabled community in Dubai. Despite their perceived absence of a legal framework, tendency toward provision of accessible accommodations was prevalent. Uniformly, the participants focused exclusively on tourists with physical disabilities. Practical implications – There is a need for detailed and comprehensive legislation protecting the rights and needs of disabled tourists, particularly in view of Dubai's successful bid to host Expo 2020. This need will, no doubt, be fulfilled in light of the recent announcement that Dubai will enact its own disability law intended to make the emirate fully accessible to persons with disabilities. Originality/value – Research into the rights and needs of the disabled community has been largely overlooked in the Middle East, an oversight which is due for correction by virtue of an anticipated increase in tourism numbers in Dubai. The opportunity exists for enactment of model legislation taking into account the needs of disabled tourists, expectations of local industry, realities of the marketplace and regional cultural influence.